2005
DOI: 10.1111/j.1398-9995.2005.00735.x
|View full text |Cite
|
Sign up to set email alerts
|

Exhaled nitric oxide in a population‐based study of asthma and allergy in schoolchildren

Abstract: Exhaled nitric oxide (NO) reflects inflammation in the lower airways and is well adapted for use in children. The aims of this study were to investigate the distribution of the fraction of expired NO (FENO) in school children and to compare FENO and spirometry in relation to the International Study of Asthma and Allergies in Childhood questionnaire. The study was performed in 959 randomly selected 13-14-year-old school children in Uppsala, Sweden. Exhaled NO was measured at an inhalation rate of 0.1 l/s (FENO0… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
46
3
3

Year Published

2006
2006
2014
2014

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(64 citation statements)
references
References 26 publications
12
46
3
3
Order By: Relevance
“…This result is in agreement with the works of Barreto et al 4 and Wong et al, 16 who recently demonstrated a sex difference in eNO levels in schoolchildren. Similarly, Nordvall et al, 17 in a large population sample, found a significantly higher eNO in boys than in girls. The authors attributed this finding to a possible role of larger lung volumes in boys.…”
Section: Discussionmentioning
confidence: 68%
“…This result is in agreement with the works of Barreto et al 4 and Wong et al, 16 who recently demonstrated a sex difference in eNO levels in schoolchildren. Similarly, Nordvall et al, 17 in a large population sample, found a significantly higher eNO in boys than in girls. The authors attributed this finding to a possible role of larger lung volumes in boys.…”
Section: Discussionmentioning
confidence: 68%
“…Studies have been developed using HS-SPME in order to establish the volatile composition of human exhaled breath [8] or for a specific type of disease, for example diabetes [14], lung cancer [15] and cystic fibrosis [16] or for chemical substances exposure monitoring [17]. Studies concerning non invasive monitoring of allergic airway inflammation have been made using exhaled nitric oxide [18] or breath condensate [19]. The lack of a prominent HS-SPME study in allergic asthma exhaled breath led us to develop an experimental design by combining HS-SPME with gas chromatography-quadrupole mass spectrometry (GC-qMS) to assess information from allergic asthma metabolomic patterns.…”
Section: Introductionmentioning
confidence: 99%
“…[15][16][17] There was no agreement as to whether the presence of symptoms was higher in the atopic patient. In the present study, no statistically significant difference was observed between the groups; however, some authors have described such significance.…”
Section: Discussionmentioning
confidence: 64%
“…16 These levels are elevated in asthmatic patients, with rates 1.6 to 4.4 times greater than those found in healthy individuals. 17 During treatment with inhaled or systemic corticosteroids, these levels decrease or even return to normal.…”
Section: Exhaled Nitric Oxide Measurementmentioning
confidence: 99%